An advanced mean field dislocation density reliant physical model to predict the creep deformation of 304HCu austenitic stainless steel. (August 2022) - Mehrotra, Pankhuri; Kumar, Nilesh; George, Alphy; Sahoo, Kanhu Charan; Ganesan, Vaidyanathan; Ahmadi, Mohammad Reza; Trivedi, Shivam; Yadav, Surya D.
Abstract: Physical based creep modelling enables to understand the life-limiting factors that are required for a safe and economic operation of power plant components. Thus, herein an improved physical approach to address the creep behavior of 304HCu austenitic stainless steel is presented. This approach combines a dislocation density reliant physical model with a continuum damage mechanics (CDM) model. Two different dislocation densities: mobile and forest, and dislocation mean free path are used to describe the substructure in order to model the creep strain. The original Orowan's equation for estimating creep strain rate is modified employing CDM based softening parameters to take account of damage causing tertiary creep. The model is advantageous in the sense that with the ongoing creep, the evolution of different variables that are dislocation densities, dislocation mobility, dislocation velocity, internal stress, effective stress and damage evolution is tracked and discussed thoroughly. Furthermore, the model output is corroborated with experimental creep data of 304HCu steel. The predicted values of forest dislocation density, mobile dislocation density, mean free path, internal stress, effective stress, dislocation mobility and dislocation velocity are in the range of 7.91 × 10 11 – 1.01 × 10 13 m −2, 8.16 × 10 10 – 4.56 × 10 11 m −2, 9.35 – 9.80 µm, 11.70 – 35.50 MPa, 86.0 – 165.0 MPa, 1.68 × 10 −9 – 2.11 × 10 −7 Pa −1 s −1 and 6.48 × 10 −11 – 7.45 × 10 −9 m/s, respectively, at the end of simulation. Graphical Abstract: ga1 Highlights: A new physical based model to address the creep deformation of 304HCu SS. Internal variables: mobile and forest dislocation densities, and mean free path. Theoretical creep curves are validated with experimental curves. The evolution of dislocation densities, dislocation mobility, velocity of dislocations, internal stress, effective stress and damage parameters is tracked and discussed all together thoroughly.